Looking at Patent Law: Detecting Crevice Corrosion in Seawater Piping Systems Using an O-Ring Sensor-A Case Study. (1st September 2022) - Jennings Taylor, E.; Maria
Abstract : In this installment of the "Looking at Patent Law" series, we present a case study of the prosecution events of U.S. Patent No. 5, 865, 971 directed toward "Sealing Ring with Electrochemical Sensing Electrode." This invention aligns with several divisions of the Electrochemical Society (ECS), including Corrosion (CORR), Industrial Electrochemistry and Electrochemical Engineering (IE&EE), and Sensor (SENS). Notably, the development team for the o-ring crevice corrosion sensor included many members of the ECS. The case study begins with a brief synopsis of the background of the invention followed by 1) summary of key drawings and the specification of the invention, 2) inventor assignment and power of attorney designations, 3) submission of the Invention Disclosure Statement (IDS) and associated Duty of Candor, 4) summary of the non-final office action (NF-OA) and rejection, and 5) applicant response and allowance of the patent application. The case study illustrates the use of a professional search of the prior art and the applicant providing a summary of the prior art in a "Statement of Relevancy." The "Statement of Relevancy" allowed the applicants to provide a convincing summary of the prior art to the USPTO and to craft well-defined claims avoiding rejections based on lack of novelty and obviousness. With this case study, we hope to de-mystify the patent prosecution process and better prepare electrochemical and solid-state scientists, engineers and technologists to interact with their patent counsel regarding their inventions.